THE COMPARISON OF THE CUMULATIVE GRADE POINT AVERAGE ON MEDICAL STUDENTS LIVING IN DORMITORY AND BOARDING HOUSE OF A MEDICAL SCHOOL - Resiana Karnina (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: In educational institution, learning achievement is an important indicator to measure the success of the learning process. Academic achievement can be defined as a result of the work that has been achieved by someone in his learning process, which is avoud as a GPA (Grade Point Average) in Higher Education or collage. Many factors that affect the value of GPA one of them comes from external factors ie residence. Medical Program Student of University of Muhammadiyah Jakarta is free to stay in dormitory or boarding house (indekos) during lectures in Faculty of Medicine and Health University of Muhammadiyah Jakarta. The purpose of this research is to determine the comparison and relationship of the Cumulative GPA on Students Living in Dormitory and Boarding House (Indekos) at Medical University of Muhammadiyah Jakarta Class of 2016. Method: This research uses quantitative analytic research type with cross sectional study. The subject of this research is a Student of Medical Studies at University of Muhammadiyah Jakarta. The Analysis was done by Mann Whitney Test. Results: There was no correlation between cumulative GPA in Students Living in Dormitory with Indekos with p value 0,292. Conclusion: There was no correlation between residence’s respondent and cumulative grade point of respondents in the research, but with Mann-Whitney test results comparing the rankings between groups, respondents with residence showed that the possibility of cumulative GPA is better than those living in the dormitory.